Risks of thromboembolism, mortality and bleeding in 2, 435, 541 atrial fibrillation patients with and without cancer: a nationwide cohort study. (24th May 2021) - Pastori, D; Marang, A; Bisson, A; Menichelli, D; Herbert, J; Lip, GYH; Fauchier, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Atrial fibrillation (AF) and cancer are frequently coexisting in clinical practice. The impact of cancer on outcomes in AF patients is unclear as well as the performance of HAS-BLED and CHA2DS2-VASc scores. Purpose. To investigate the incidence rate (IR) of all-cause and cardiovascular mortality, ischemic stroke (IS), major bleeding and intracranial haemorrhage (ICH) according to the presence of cancer and cancer types. Methods: Observational retrospective cohort study including 2, 435, 541 AF patients. Results. Overall, 399, 344 (16.4%) had cancer, the most common being metastatic, prostatic, colorectal, lung, breast, and bladder (figure). The table shows the IR of bleeding and ischemic outcomes according to the cancer type. During 2 years follow-up, the IS was higher with pancreas, uterine and breast cancers. Cancer increased major bleeding (HR 1.27, 95%CI 1.26-1.28) and ICH (HR 1.07, 95%1.05-1.10), which progressively increased by HAS-BLED score, which showed generally good predictivity (c indexes >0.70). The CHA2DS2-VASc score showed slightly lower predictivity in AF cancer patients. Conclusions. Cancer increased all-cause and cardiovascular mortality, major bleeding and ICH risk in AF patients. The association between cancer and IS differed among cancer types.